Pathogenic variability in Xanthomonas oryzae pv oryzae in Bangladesh - JALALUDDIN, M; KASHEM, M A (The Indian Journal of Agricultural Sciences, 2013)
Pathogenic variability of 40 isolates of Xanthomonas oryzae pv oryzae obtained from flag leaf samples of bacterialleaf blight in rice (oryza sativa L.) collected from different districts in Bangladesh was studied. The pathogenic variabilitywas tested on to seedlings of the five differential varieties of rice, viz 'BR 14', 'Iratom 24', 'TKM 6', 'BR 3' and 'BR 9'.Twelve races of Xanthomonas oryzae pv oryzae were identified in different districts in Bangladesh. Among the races, therace 11 was commonly distributed in the districts Comilla, Mymensingh, Bogra and Gazipur followed by race 12 whichwas common in the districts Dhaka, Mymensingh and Gazipur. The most frequently occurring race was race 7 followedby race 11. Flag leaf inoculation tests on a susceptible cultivar 'BR 9' and a moderately resistant cultivar 'BR 14' revealedthat there were six and seven virulence groups of Xanthomonas oryzae pv oryzae, respectively, existing in Bangladesh.